Advances in Small-Molecule C-KIT/PDGFRα Inhibitors for the Treatment of Gastrointestinal Stromal Tumors - Xuan Zheng; Hong Liang; Yang Zhou; Xiaoyun Lu (Pharmaceutical Fronts)
Stem cell factor receptor (C-KIT) or platelet-derived growth factor receptor α (PDGFRα) gene mutations have been identified as oncogenic drivers for most gastrointestinal stromal tumors (GISTs). Thus, small-molecule inhibitors of C-KIT or PDGFRα have emerged as effective treatments for GISTs. Although the currently approved first- to fourth-line drugs are initially effective against GISTs, the inevitable development of drug resistance remains an unmet challenge. To address secondary mutations leading to drug resistance, several novel selective C-KIT/PDGFRα small-molecule inhibitors have been developed and clinically studied. This review summarizes the pathogenesis, treatment, and drug resistance mechanisms of GISTs and briefly describes current challenges and future efforts for GIST treatment using small-molecule kinase inhibitors.